Tools of Intertextuality in Discourse of Social Advertising - M. V. Terskikh (Научный диалог)
The article is devoted to the study of the tools of intertextuality in the discourse of social advertising. Despite the high interest of researchers to the problem of the intertextual interaction the question of the mechanism of intertextuality in advertising, including social, is still not fully lit, especially as the advertising is dynamic and each new day provides ample material for research. The novelty of the research is determined by the author’s study of modern tools of intertextuality in the discourse of social advertising, the main objectives of which consist in formation of system of values in the mass consciousness, the adjustment of the value priorities and benchmarks, translation of socially approved behavioral patterns. That’s why social advertising needs the non-stereotypical representation of its object - social ills and values. Special attention is paid to the typology of the tools of intertextuality in the texts of social advertising and the functional load of each of the considered types. As the basic functions of intertextual inclusions in the discourse of social advertising the author identifies attractive and persuasive ones as the most important and regularly implemented. As secondary functions, aesthetic, game and delimitation ones are highlighted. Suggested classifications are accompanied by examples of Russian and foreign social advertising.